West Kalimantan Recreational Sports Policy Evaluation - Adiyudha Permana; Achmad Sofyan Hanif; Yusmawati Yusmawati; Whalsen Duli Agus Lauh (Kinestetik : Jurnal Ilmiah Pendidikan Jasmani, 2022)
Recreational sports policy is a product of efforts made by sports organizations to meet the needs of community sports activists. Policies in each regional sport vary according to the region. This research aims towork programs, human resources, availability of facilities, and technical assistance in recreational sports in West Kalimantan Province. This research was carried out at the center of the West Kalimantan Province government in the field of sports, namely the Youth Sports and Tourism Office of West Kalimantan Province and the secretariat of the Indonesian Community Recreational Sports Committee (KORMI) West Kalimantan Province.. The method used ismixed methods research (MMR). The type of research isCIPP model evaluation model (Stufebeam's). Sampling technique with purposive sampling. The number of samples is 48 respondents. Data collection techniques are indirect communication, direct communication, and documentary study techniques. The analytical techniques used in qualitative research are data reduction, data presentation, and drawing conclusions. Analysis on the quantitative approach is the percentage and interval values. The results showed that the work program of the West Kalimantan Recreational Sports Organization had an average percentage value of 83.1% in the Very High category. The human resources of the West Kalimantan Recreational Sports Organization have an average percentage value of 83.9% in the Very High category. West Kalimantan Recreational Sports facilities have an average percentage value of 76.7% in the High category.